Modernity and exclusion - Kahn, Joel S. (Theory, culture & society, 2001)
This text re-examines the project of modernity by opposing the abstract, idealized vision of modernity with an alternative ethnographic understanding. The book draws out the specific cultural and religious assumptions underlying popular modernism